Immersive Pedagogy: The Impact of Virtual Reality (VR) Simulations on STEM Learning Retention - Andy Rachman; Putri Julia Ningsi; Ren Suzuki (Yayasan Adra Karima Hubbi, 2026)
Background. Education in STEM disciplines faces persistent challenges related to engagement, conceptual understanding, and long-term retention, as conventional instructional methods often fail to provide interactive, contextually rich experiences necessary for deep learning. Recent advances in immersive technologies, particularly Virtual Reality (VR), offer the potential to bridge this gap by providing learners with interactive, multisensory environments that enhance understanding and cognitive retention. Purpose. The study aimed to investigate the impact of VR simulations on undergraduate students’ STEM knowledge retention and to identify specific features of immersive pedagogy that contribute to durable learning outcomes, while further seeking to provide actionable guidance for integrating VR into higher education curricula effectively. Method. A quasi-experimental design was employed, involving 120 undergraduate students divided into an experimental group exposed to VR simulations and a control group receiving conventional instruction. Data collection included pre-tests, immediate post-tests, delayed post-tests, observational records, and platform analytics, which were analyzed using statistical techniques including paired-sample t-tests and ANCOVA to assess the significance and magnitude of learning gains. Results. Results indicated that VR participants achieved significantly higher immediate and delayed post-test scores, particularly on conceptual and application-based items. Engagement metrics and observational data corroborated enhanced cognitive involvement and sustained learning. Conclusion. Findings confirm that immersive pedagogy via VR significantly improves STEM retention and provides a scalable, evidence-based approach for enhancing higher education instruction.